Learning and growing: an alternative strategy to teach English - Paulus Subiyanto; Ni Ketut Suciani; I Nyoman Rajin Aryana; Gusti Nyoman Ayu Sukerti; Anak Agung Raka Sitawati (English, 2018)
One of the problems faced by ESL learners is not a linguistic one, but they are afraid to express what they know and feel, in English. They are afraid of making mistake and prefer keeping passively attitude to participating actively in learning activities. They have less self-confidence to speak English though they have enough linguistic knowledge and skill. Therefore, it is important to find a strategy to break such “ice” in order to overcome psychological impediment faced by the learners. Thus, learning English is simultaneous with a growing personality. This article is based on the classroom experience by experimenting with the method called Learning and Growing (L&G). The basic principle of this method is how to motivate the learners talking about themselves, or things close to them. The method enables them to know who they are, to accept themselves, and to feel their self-confidence. After practicing one topic, e.g. Who Am I, the learners are able to accept themselves and have an awareness that making mistake is normal in the learning process. As the result, they dare to share who they are without being afraid to make mistake linguistically. The other principle is how to make relax atmosphere of learning, ignoring some formal rules. A friendly relationship is built during the learning process both the learner-learner and the teacher-learner. The teacher’s task is to choose the topics with double goals: language and psychology. What language skill will be achieved and what personal growth will be focused on are the vital concern of the teacher. These goals will be realized by making an appropriate lesson plan and preparation. Finally, the evaluation may be conducted, especially for language achievement. The main purpose of this evaluation would rather know if the goal has been achieved than to get grades.